2004
DOI: 10.1086/381261
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Maintenance Therapy for Cryptococcal Meningitis in Patients with AIDS Treated with Highly Active Antiretroviral Therapy: An International Observational Study

Abstract: We conducted a retrospective, multicenter study evaluating the safety of discontinuing maintenance therapy for cryptococcal meningitis after immune reconstitution. Inclusion criteria were a previous definitive diagnosis of cryptococcal meningitis, a CD4 cell count of >100 cells/microL while receiving highly active antiretroviral therapy (HAART), and the subsequent discontinuation of maintenance therapy for cryptococcal meningitis. The primary end point was relapse of cryptococcal disease. As of July 2002, 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 27 publications
3
55
0
3
Order By: Relevance
“…This continues lifelong or until sufficient immune reconstitution has taken place. Although international data 14 suggest that prophylaxis in patients on HAART may be discontinued at a CD4 count of 100 cells/L, it might be safer to continue until the CD4 count is above 200 cells/L since no data exist for our patient population. Primary prophylaxis does not form part of any southern African guidelines, but can be considered for selected patients.…”
Section: Fluconazole Prophy-laxis Indicationmentioning
confidence: 98%
“…This continues lifelong or until sufficient immune reconstitution has taken place. Although international data 14 suggest that prophylaxis in patients on HAART may be discontinued at a CD4 count of 100 cells/L, it might be safer to continue until the CD4 count is above 200 cells/L since no data exist for our patient population. Primary prophylaxis does not form part of any southern African guidelines, but can be considered for selected patients.…”
Section: Fluconazole Prophy-laxis Indicationmentioning
confidence: 98%
“…Several prior studies have shown that it is acceptable to stop cryptococcal suppressive therapy in patients who have a sustained immunological response to HAART [22][23][24]. Therefore, we would expect improved immunological function to result in a decrease in both the prevalence and the incidence of cryptococcosis.…”
Section: Prevention Of Cryptococcosis 255mentioning
confidence: 99%
“…This has been demonstrated to effectively reduce rates of relapse from ~ 40 % to less than 5 % in the pre-HAART era [78]. Secondary prophylaxis can be discontinued after 1-2 years of antifungal therapy in patients who respond to HAART with rise in CD4 + cell counts to greater than 100 cells/µl and decline in viral load (HIV RNA) to undetectable levels for at least 3 months [62,79,80].…”
Section: Host Considerations Cryptococcal Meningitis In Hiv Patientsmentioning
confidence: 99%